Hybrid barn: the switch from a naturally to a mechanically ventilated turkey barn to protect from harmful bioaerosols - Sake, Björn; Butenholz, Kira; Kempf, Katrin; Kemper, Nicole; Schulz, Jochen (Frontiers in Veterinary Science, 2025)
IntroductionAnimal health is essential to ensure the highest level of animal welfare and to conserve resources. Especially in naturally ventilated barns, the airborne entry of pathogens is difficult to avoid. For instance, birds in naturally ventilated turkey barns are frequently infected by highly pathogenic avian influenza and the airborne route may play a role. In this study, a naturally ventilated turkey barn was equipped with filter modules that allow a conversion to a mechanically ventilated barn.MethodsFour filter modules with two filter stages were adapted to a turkey barn and the curtains were closed to induce a slight overpressure in the barn. Air samples were taken over the course of 16 months in front of and behind the filter units to assess the filter efficiencies. Filter efficiencies were evaluated by the reduction of particle classes (PM1, PM10, nanoparticles), microorganisms (total bacteria, molds, yeasts), and the detection of potentially pathogenic bacteria and viruses by PCR tests.ResultsParticle reduction rates were 94.17% for PM1, 94.27% for PM10, and 95.80% for nanoparticles, respectively. Total bacteria counts were reduced by 95.88%, molds by 94.64%, and yeasts by 66.03%. Ornithobacterium rhinotracheale was significantly retained in the filter units. The results for influenza A also indicated that the entry of potentially infectious particles could be prevented.DiscussionThe flexible switch from a naturally to a mechanically ventilated barn with filtered supply air can be an innovative solution to avoid airborne pathogen entry in risky situations and may represent a component in the strategy to control epidemic diseases.